Evaluation of Shear Bond Strength of Composite to Feldspathic Porcelain after Porcelain Surface Treatment with CO2 and Er:YAG lasers - Mehdi Shirinzad; Reza Fekrazad; Loghman Rezaei-Soufi; Ebrahim Yarmohammadi; Shahriar Jalalian (Journal of Islamic Dental Association of Iran, 2013)
Background and Aim : Fractured ceramic crowns can sometimes be repaired with composite resin. The aim of the current study was to determine the shear bond strength of composite to feldspathic porcelain after CO2 and Er:YAG laser porcelain surface preparation .